Crystalline Porous Organic Salts: From Micropore to Hierarchical Pores. Issue 44 (15th September 2020) - Yu, Shen; Xing, Guo‐Long; Chen, Li‐Hua; Ben, Teng; Su, Bao‐Lian
Abstract: Crystalline porous organic salts (CPOSs), as an emerging class of porous organic materials, combining the uniform microporous system and distinct polarized channels, have become a highly evolving field of important current interest. The unique ionic bond of a CPOS endows the confined channels with high polarity, making CPOSs distinct from other organic frameworks. CPOSs show many fascinating properties, such as proton conductivity and fast transport of polar molecules, which involve the interaction between highly polarized guest molecules and host frameworks. Substantial progress has been made in the synthesis and applications of CPOSs. Herein, an overview is provided to impart a comprehensive understanding of the link between the synthetic approaches and the resultant microporous structure, the structure–function correlation and the state‐of‐the‐art applications of CPOSs. The enhanced mass‐transport performance of hierarchically porous structure in combination with the intrinsic polarized channels of CPOSs is very promising to create new applications and contribute to a new research upsurge. The perspective to construct porous hierarchy within the crystalline porous organic salts is assessed and will open a new research avenue. In the conclusion, the current challenges on the synthesis, structural regulation, and applications of CPOSs and the future of hierarchically porous crystalline organic salts are discussed. Abstract : An overview of recent achievements in the synthetic approaches, structural features, and state‐of‐the‐art applications of crystalline porous organic salts (CPOSs) and a perspective on the construction of the porous hierarchy within the CPOS frameworks are described.